A conceptual framework for assessing socio-hydrological resilience under change - Mao,F; Clark,J; Karpouzoglou,T; Dewulf,A; Buytaert,W; Hannah,D (2016)
Abstract. Despite growing interest in resilience, there is still significant scope for increasing its conceptual clarity and practical relevance in socio-hydrological contexts. Specifically, questions of how socio-hydrological systems respond to and cope with perturbations and how these connect to resilience remain unanswered. In this paper, we propose a novel conceptual framework for understanding and assessing resilience in coupled socio-hydrological systems. Taking a systems perspective, we argue resilience is a set of systematic properties with three dimensions: absorptive, adaptive and transformative, and contend that socio-hydrological systems can be viewed as various forms of human-water couplings, reflecting different aspects of these interactions. We propose a framework consisting of two parts. The first part addresses the identity of socio-hydrological resilience, answering questions such as ‘resilience of what in relation to what’. We identify three framings of resilience for different types of human-water systems and subsystems: (1) the water subsystem, highlighting hydrological resilience to anthropogenic hazards; (2) the human subsystem, foregrounding social resilience to hydrological hazards; and (3) the coupled human-water system, exhibiting socio-hydrological resilience. We argue that these three system types and resiliences afford new insights into the evaluation of different water management challenges. The first two types address hydrological and social states, while the third type emphasises the feedbacks and interactions between human and water components within complex systems subject to internal or external disturbances. In the second part, we focus on resilience management and develop the notion of the ‘resilience canvas’, a novel heuristic device to identify possible pathways and to facilitate the design of bespoke strategies for enhancing resilience in the socio-hydrological context. The ‘resilie